Influence of millet varieties on fertilizer application rates and plant spacing in Sudan savanna - Abdulrahman Ibrahim; Mannir Isah Kerau (African and Mediterranean Agricultural Journal - Al Awamia)
In order to find out how different pearl millet varieties affect fertilizer application rates and plant spacing in the Sudan savanna of Nigeria, two field experiments were carried out in a purely sandy loamy soil environment at the teaching and research farm of the Basic Vocational Agriculture School Tambu-Daura situated at 120 59'34 N, 80 16'58 E, and 549 meters above sea level) in Katsina State, Nigeria in the growing seasons of 2022 and 2023. Three different varieties of pearl millet (DANDIGALI, JIRANI, and SOSAT) were used in the trial, along with two plant spacing (50 cm and 70 cm) and two different fertilizer application rates (100:50:50 and 80:40:40). The treatments were factorized and placed under a Randomize Complete Block Design (RCBD) with three replications. Throughout the experiment, data on yield-related components were recorded. Based on the results, it is confirmed that the variety DANDIGALI recorded the greatest values for Total yield per hectare (1981 and 1823 kg/ha), Grain yield (78.50 and 75.12g), Harvest index (39.54 and 46.62%), and Biological yield (199.40 and 213.17) in both trial years. These values were significant (P<0.05). During the two trial years, a noteworthy yield value was also observed for the grain yield (77.32 and 73.43g), total yield per hectare (1978 and 1725.43 kg/ha), harvest index (41.80 and 43.31), and biological yield (187.64 and 189.69) from 50cm plant spacing. In every yield parameter examined, the measured application of fertilizer at a rate of 100:50:50 considerably (P<0.05) outperformed the application of fertilizer at a rate of 80:40:40. In conclusion, it was discovered that applying 100:50:50 and planting pearl millet DANDIGALI at 50cm plant spacing were the best and most recommended practices in the study area.